Nano-sized Cu clusters in deeply undercooled CoCuFeNiTa high entropy alloy. (1st March 2020) - Rahul, M.R.; Samal, Sumanta; Marshal, A.; Balaji, V.I. Nithin; Pradeep, K.G.; Phanikumar, Gandham
Abstract: The non-equilibrium response of a high entropy alloy CoCuFeNiTa0.5 has been studied using undercooling as a control parameter. The solidification growth rates are rapid (30–50 m/s) at deep undercooling (>150 °C) and are comparable with conventional alloys. The elemental segregation especially that of Cu as predicted by phase field simulations in lower (<50 °C) undercooling regime matches with the experimental observations. This study indicates that even extreme non-equilibrium conditions during solidification could not avoid elemental segregation at the atomic scale. Graphical abstract: Image, graphical abstract